Estimation of the risk factors for falls in the elderly: Can meta-analysis provide a valid answer? - Bloch, Frederic; Thibaud, Marie; Tournoux-Facon, Caroline; Brèque, Cyril; Rigaud, Anne-Sophie; Dugué, Benoit; Kemoun, Gilles (Geriatrics & gerontology international, 2013)
The objective of this study was to analyze whether a meta‐analysis could allow us to draw useful conclusions about the risk factors for falls in the elderly. A systematic review was carried out of various databases and completed manually. To satisfy the inclusion criteria, an article had to examine a population of subjects aged over 60 years to pertain to falls occurring during daily living activities, and to involve observational or interventional studies. This review identified 4405 indexed articles published between 1981 and 2011. Of the 220 studies with available data that were included in the final study, just 4% were interventional. Among these 220 studies, just 45% offered a satisfactory level of scientific proof. In total, 88 meta‐analyses were carried out on the 156 potential protectors or risk factors that were identified. Our systematic review and meta‐analyses ensured that high‐quality results were obtained from this comprehensive literature search and included a detailed assessment of the quality of the included studies. Several factors appeared to be disproportionately represented in the literature, a fact that likely reflects the objective and precise assessment of these factors rather than their importance in the falls of the elderly. Thus, we cannot be certain that we obtained the most comprehensive analysis of the risk factors for falling with this method. Meta‐analyses can help to define the association between falls and various risk factors, but they have to be used complementary to systematic review for the assessment of risk factors. Geriatr Gerontol Int 2013; 13: 250–263.